Research on efficiency of telephone networkswith different structures - Chaban, Ksenia; Labа, Hanna; Tchaikovskyi, Ihor (Publishing House of Lviv Polytechnic National University, 2014)
With the development of communication networks, their structures have also evolved and improved. Today the prospective development and construction of telephone networks of all levels of hierarchy calls for insight into their structures. The aim of this paper is determination and analysis of the efficiency of the most widespread structures of public telephone networks according to specific criteria for effectiveness. The paper sets the following tasks: 1) to analyze the most common structures of telephone networks and to build them on a particular area taking into account the initial data and methods for nodes locating; 2) to establish parameters of the telephone networks efficiency; 3) to calculate the chosen parameters for the building of structures and conduct a quantitative and qualitative analysis of the results obtained. The relevancy of this work is explained both by the lack, in scientific literature, of quantitative research into the parameters of efficiency of telephone networks with different structures and by practical needs related to the common use of various structures of the communication networks. З розвитком мереж зв’язку розвивалися й удосконалювалися структури мереж. Сьогодні перспективний розвиток телефонних мереж усіх рівнів їєрархії передбачає дослідження структур для їх побудови. Метою цієї роботи є побудова й аналіз ефективності найбпоширеніших структур телефонних мереж загального користування згідно з визначеними критеріями ефективності. У роботі поставлені завдання: 1) дослідити найпоширеніші структури телефонних мереж та побудувати їх на конкретній території з урахуванням вихідних даних і методів розташування вузлів; 2) обґрунтувати параметри ефективності телефонних мереж; 3) розрахувати вибрані параметри для побудованих структур і провести кількісний та якісний аналіз отриманих результатів. Актуальність цієї роботи пояснюється як відсутністю в літературі кількісного дослідження параметрів ефективності телефонних мереж з різними структурами, так і потребами практики, пов’язаними з широким застосуванням різних структур мереж зв’язку.
Дослідження ефективності телефоннихмереж із різними структурами
Keywords: telephone network with channel switching; digital switching system; network structure; reliability; bandwidth